The Narrative of Women in Prison: The Parenting Practices and the Concepts of Mother in Incarcerated Women - Ulya Saida; Elizabeth Kristi Poerwandani (Sawwa: Jurnal Studi Gender, 2020)
This article discusses the experiences of incarcerated women regarding parenting practice in prisons and the concept of motherhood. With the narration of eight women who were pregnant or breastfeeding and serving their sentences at the Pondok Bambu Detention Center in East Jakarta, the researcher presented different viewpoints of women by listening to their stories even though they had committed criminal acts. This research uses a qualitative approach to gender perspective. The researchers did field observations during the data collection process. Parenting practices carried out in prison was not done without obstacles. There are obstacles in terms of knowledge as a mother, economic, and emotional side experienced by incarcerated women. These obstacles influence the concept of thinking of imprisoned women regarding social construction to be a good mother. They always try to look decent to be able to nurse their children with their conditions in prison. Some of them said the presence of their children in detention is like a new spirit in their life.